Microbiological and Chemical Quality of Portuguese Lettuce—Results of a Case Study - Catarina Ferreira; Filipa Lopes; Reginaldo Costa; Norton Komora; Vânia Ferreira; Virgínia Cruz Fernandes; Cristina Delerue-Matos; Paula Teixeira (Foods, 2020)
In addition to environmental pollution issues, social concerns about the sustainability, safety, and quality of conventionally grown fruits and vegetables have been increasing. In order to evaluate if there were any microbiological differences between samples of organic and conventional lettuce, a wide range of parameters were tested, including pathogens and indicator organisms: the enumeration of Escherichia coli; the detection of Salmonella spp.; the detection/enumeration of Listeria monocytogenes; the enumeration of lactic acid bacteria, Pseudomonas spp. yeasts and molds, and Enterobacteriaceae. This study also evaluated the chemical safety of the lettuce samples, quantifying the nitrate concentration and 20 pesticides (14 organochlorine and 6 organophosphorus pesticides). Significant differences (p < 0.05) between the conventional and organic samples were only detected for the counts of total microorganisms at 30 °C. Pathogens were absent in all the samples. The analytical method, using the quick, easy, cheap, effective, rugged, and safe (QuEChERS) approach for pesticide extraction, was suitable for detecting the targeted analytes; the limit of quantification (LOQ) was between 0.6 and 1.8 µg/kg (lower than the Maximum Residue Levels (MRLs) established by EU legislation). In three organic lettuce samples, one organochlorine pesticide (α-HCH) was observed below the MRLs. For the samples analyzed and for the parameters investigated, except for the total mesophilic counts, the organic and conventional lettuces were not different.